Intrafetal laser therapy in a monochorionic diamniotic triplet pregnancy with two acardiac fetuses: a case report and literature review - Huang, Guiqiong (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Monochorionic diamniotic triplet pregnancies are rare. Twin reversed arterial perfusion sequence in monochorionic triplet pregnancies is extremely rare, and it is associated with high perinatal morbidity and mortality rates in the “pump fetus.” CASE PRESENTATION: We reported a case of monochorionic diamniotic triplet pregnancy with twin reversed arterial perfusion sequence, including two acardiac fetuses sharing a single amniotic sac and a normal fetus in another amniotic sac. Due to rapid growth of the acardiac fetuses, intrafetal laser therapy was performed in both of them under ultrasound guidance at 15 weeks +5 days. Subsequently, regular and careful antenatal care including fetal ultrasonography and doppler and fetal echocardiography was conducted. At 37 weeks +4 days, a healthy female baby weighing 2510 g was delivered. The baby was followed up and now at 11 months old is in good health. CONCLUSIONS: Twin reversed arterial perfusion sequence in monochorionic triplet pregnancy should be diagnosed early by ultrasound imaging during pregnancy. Individualized management should be based on clinical conditions to improve the perinatal outcome of the pump twin. Intrafetal laser therapy could be an alternative procedure when intrauterine intervention is required.